Commentary on Song of songs - Levi ben Gershom, 1288-1344 (Yale Judaica series, 1998)
Rabbi Levi Ben Gershom (Gersonides, 1288-1344), one of medieval Judaism's most interesting figures, was known not only as a philosopher, exegete, and halakhist but also as a contributor to the fields of astronomy and mathematics.